Manajemen Epilepsi pada Kehamilan - Taufiqurrohman, Agus; Nuradyo, Damodoro; Harsono, Harsono (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2009)
Epilepsy is recognized as the commonest serious neurological disorder in the world. Women with epilepsy  experience several gender-related physical and social problems. They constitute high obstetric risk because of reduced fertility, risk of seizures during pregnancy, and complications of pregnancy. Hormonal and other factors can alter the pharmacokinetics of antiepileptic drugs during pregnancy and puerperium. Antenatal exposure to antiepileptic drugs, particularly at higher dosage and in polytherapy, increases the risk of fetal malformation. Recent reports raise the possibility of selective developmental language deficits and neurocognitive deficits with antenatal exposure to antiepileptic drugs. There are concerns regarding the effect of traces of antiepileptic drugs that pass to the infant during breast-feeding. The pre conception management is the cornerstone for epilepsy care in Women with epilepsy. A careful reappraisal of each case should ascertain the diagnosis, the need for continued antiepileptic drugs therapy, selection of appropriate antiepileptic drugs, optimization of the dosage, and prescription of folic acid. During pregnancy, the fetal status needs to be monitored with estimation of serum a-feto-protein and ultrasound screening for malformations. The dosage of antiepileptic drugs can be adjusted according to clinical requirement and blood levels of antiepileptic drugs. Several institutions recommend oral vitamin K toward the end of pregnancy when enzymeinducing.Key Words : epilepsy, pregnancy, management, complication